If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 11x = 27 + x Solving 7 + 11x = 27 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7 + 11x + -1x = 27 + x + -1x Combine like terms: 11x + -1x = 10x 7 + 10x = 27 + x + -1x Combine like terms: x + -1x = 0 7 + 10x = 27 + 0 7 + 10x = 27 Add '-7' to each side of the equation. 7 + -7 + 10x = 27 + -7 Combine like terms: 7 + -7 = 0 0 + 10x = 27 + -7 10x = 27 + -7 Combine like terms: 27 + -7 = 20 10x = 20 Divide each side by '10'. x = 2 Simplifying x = 2
| 700=x-x*.04 | | 2x+21=9x-61 | | 10=2+1q | | 10=20-5q | | 8=2+1q | | 8=20-5Q | | 34+5y-14=15y-12-2y | | 5=2+1q | | 5=20-5q | | 3=2+1q | | .12n=.32n | | 120(5y+2x)=30 | | 3t-19=-1+9t | | 6t-28=-27+7t | | 11x+4y=121 | | 2x+5x=120 | | 75x-9y=24 | | 6n+6=4n | | 6n=24n | | -6*(x+1)-17=15+4 | | 24+3y-3=14y-9-5y | | 7*250= | | 4a-a=-2 | | 2+3x(x+1)=8 | | 700=x+x*.04 | | 2*(a-7)= | | 5c+7g=-48 | | 3s-2m=-33 | | g(x)=x^2+4x-5findg(-4) | | g(x)=x^2+4x-5 | | 7x+5-6x=10 | | 7=-0.4x(x-10) |